Pendidikan Karakter Menuju SDM Paripurna - HM, Muhdar (Al-Ulum, 2013)
The main objective of this article is to elucidate how character education in Islamic perspectivewhich creates outstanding human resource. Educational Character in Islam perspective is the education that set plenary human attitude and character on intellectual Questions (IQ), emotional Question (EQ), and spiritual Question (SQ). The totality of these IQs will form a perfectman, whichin Islam it isnamed â€œinsÃ¢n kÃ¢milâ€ or plenary human resource. Intellectual Question (IQ) forms rational thought. While emotional question is emotional which be one impulsive understanding system and have big effect, yet it is sometimes not logic. Both of these thought work in harmony and complete each other. Spiritual Question (SQ) is spiritual intelligence which forms human thought into truth in Islam term â€œshiddiqâ€, faithful â€œistiqamahâ€, believable â€œamanahâ€, â€œfathanahâ€ and â€œtabliqâ€. The Synchronisation among Intellectual Question (IQ), and Spiritual Question (SQ) will make vertical relation between God and human (â€œHablum minallahâ€) and horizontal relation between human and human (â€œHablum minnannasâ€) which can become guidance for a responsible action in this world and the hereafter.